Advokasi dan Penyuluhan Bahaya Laten Korupsi di Masyarakat Lamagga Baubau - Farhan Farhan; Sugiono Sugiono; Suwarno Suwarno; Iin Handayani (Jurnal Kabar Masyarakat, 2023)
Corruption is a serious issue that hinders development and community welfare. The Lamagga community in Baubau faces challenges in understanding and preventing corruption due to low legal literacy and insufficient oversight of public fund management. This advocacy and counseling program aims to increase community awareness and involvement in monitoring village policy transparency. The Participatory Action Research (PAR) method, using both qualitative and quantitative approaches, was employed through seminars, workshops, digital campaigns, and the establishment of community watchdog groups.The results indicate a significant increase in public awareness of corruption, with the percentage of residents who understand the reporting mechanism rising from 25% to 68%. Community participation in village discussions also increased from 20% to 55%, demonstrating the effectiveness of community-based education. However, challenges such as resistance from local officials and cultural barriers remain obstacles that require more persuasive approaches and continuous education. Therefore, stronger synergy between the community, government, and anti-corruption institutions is necessary to ensure the sustainability of this program. By fostering closer collaboration, it is hoped that transparency and accountability in public fund management can be achieved more effectively and sustainably.